HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU PEMBERANTASAN SARANG NYAMUK PADA IBU RUMAH TANGGA DI KAWASAN PESISIR DESA HILA KABUPATEN MALUKU TENGAH - Prasetyawati Watick; Rahwan Ahmad (Jurnal Sanitasi Profesional Indonesia, 2026)
Mosquito-borne diseases remain a public health problem that requires vector control efforts through mosquito nest eradication (PSN). Knowledge is one of the factors suspected to play a role in shaping community behavior in implementing PSN. This study aims to analyze the relationship between knowledge levels and mosquito nest eradication behavior among housewives in the coastal area of ​​Hila Village, Central Maluku Regency. This study used an analytical observational design with a cross-sectional approach. The study population was all 30 housewives and all samples were taken using a total sampling technique. Data were collected using a questionnaire and analyzed univariately and bivariately using the Chi-Square test at a 95% confidence level (α = 0.05). The results showed that the majority of respondents had poor knowledge (40.0%) and poor mosquito nest eradication behavior (50.0%). Respondents with good knowledge tended to have good mosquito nest eradication behavior (72.2%), while respondents with poor knowledge tended to have poor behavior (83.3%). The chi-square test results showed a χ² value of 8.889 with p = 0.003, indicating a significant relationship between knowledge level and mosquito nest eradication behavior. This finding suggests that increased knowledge has the potential to encourage better mosquito nest eradication behavior. Therefore, increased health promotion and community education activities are needed on an ongoing basis to support vector-based disease control in coastal areas.